2010
DOI: 10.1007/s10157-010-0278-z
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase-antineutrophil cytoplasmic antibody-associated crescentic glomerulonephritis with rheumatoid arthritis: a comparison of patients without rheumatoid arthritis

Abstract: In patients with RA, MPO-ANCA-associated CrGN appeared to develop at younger ages and often showed a slowly progressive deterioration of the renal function with slight extrarenal manifestations. These smoldering clinical features may result in late referral from rheumatologists to nephrologists and therefore poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The patient in Case 1 lacked typical symptoms suggestive of vasculitis, and this might be due to the coexistence of RA. We previously reported that MPO-ANCA associated crescentic glomerulonephritis in RA patients developed in middle-aged or young adult women and was accompanied by little extrarenal manifestations [8]. Patient 1 was indeed a relatively young woman and the only symptom compatible with vasculitis was fever of unknown origin.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The patient in Case 1 lacked typical symptoms suggestive of vasculitis, and this might be due to the coexistence of RA. We previously reported that MPO-ANCA associated crescentic glomerulonephritis in RA patients developed in middle-aged or young adult women and was accompanied by little extrarenal manifestations [8]. Patient 1 was indeed a relatively young woman and the only symptom compatible with vasculitis was fever of unknown origin.…”
Section: Discussionmentioning
confidence: 91%
“…Although less common, there have been several case reports on MPO-ANCA associated glomerulonephritis in patients with RA [17][18][19][20][21][22][23]. We previously reported that renal dysfunction of MPO-ANCA associated crescentic glomerulonephritis in RA patients showed slower progression compared to typical rapidly progressive glomerulonephritis without RA [8]. The duration from onset to initiation of dialysis in Case 1 was indeed more than 1 year.…”
Section: Discussionmentioning
confidence: 92%
“…Although the patients studied had incremental increases in creatinine, their renal biopsies revealed advanced renal disease, with glomerular sclerosis and less crescent formation. It is also hypothesized that treatment with immunosuppressants, such as methotrexate and infliximab, can influence crescentic glomerulonephritis activity [5]. Our patient, however, did not receive drug therapy before presenting to the hospital.…”
Section: Discussionmentioning
confidence: 92%
“…Previous case reports describe MPO-ANCA-associated crescentic glomerulonephritis in adults between the ages of 20 and 50 [5]. Although the mechanism of action is unknown, a study by Kurita et al speculated that there is a decrease in renal function after the onset of microhematuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation